Analisis Determinan Bauran Pemasaran pada Poliklinik Rawat Jalan RSK dr. Rivai Abdullah Palembang - A Yosef Wempie; Nur Alam Fajar; Haerawati Idris (Jurnal Kesehatan, 2019)
Leprosy Hospital of dr. Rivai Abdullah Palembang in the last 3 (three) years found data on visitors who came to the Outpatient Polyclinic showed a downward trend every year since 2015. This study aims to determine the influence of patient perceptions of the marketing mix to the patient’s loyalty at Outpatient Polyclinic of Leprosy Hospital of dr. Rivai Abdullah Palembang. The study design used a cross-sectional approach, where the population in this study was outpatients in 2017. Data collection using a questionnaire that had previously been tested for validity in 30 respondents on inpatients of RSK. dr. Rivai Abdullah Palembang, samples were taken accidentally as many as 152 respondents in September - October 2018 that met the inclusion and exclusion criteria at Outpatient Polyclinic of RSK of dr. Rivai Abdullah Palembang. Data analysis used chi-square and multiple logistic regression. The results of the study showed that the 7 variables (product, price, promotion, place, people, process and physical evidence) there were 3 variables that were significant relationship with patient loyalty, namely promotion (p-value=0.005, OR=6.491), process (p-value=0,000, OR=8,796), and physical evidence (p-value=0,000, OR=12). While the product (p-value=0.335, OR=4,556), price (p-value=1, OR=0,807), place (p-value=1, OR=0,815), people (p-value=1, OR=0.815) showed there was no significant relationship with patient loyalty. The most dominant variable relationship with outpatient loyalty at Leprosy Hospital of dr. Rivai Abdullah Palembang was a physical evidence variable (OR=19,867, 95% CI 4,010 98,429).